824 The design and development of a 'hub and spoke model' for healthcare workers in the public health service in ireland. (24th April 2018) - Sisson, L; Carolan, S
Abstract : Introduction: The Health Service Executive (Ireland) Mission clearly states that people in Ireland are supported by health and social care services to achieve their full potential. It identified access, safe, compassionate and quality care as priorities. The HSE Corporate Plan 2015–2017 set our values of Care, Compassion, Trust and Learning. Methods: With proposed changes in the Irish Health Services and the development of commissioning services/service provision in the Community Healthcare Organisation/Hospital Group Model, the most effective model of care is a central governance unit i.e. WHWU with areas covered geographically by defined Area/collaborative service delivery units, this is referred to as a 'hub and spoke' model. The structure of each hub includes occupational health physician services, occupational health nursing services, employee assistance programmes, rehabilitation services, health promotion, health and safety, and the provision of governance and support. The targets for the area/collaborative service delivery units, 'hub and spoke' model will be exactly as described by the Healthy Staff, Better Care for Patients. www.dh.gov.uk 2011. Result: This model of care will be implemented over Q.2 2017 to Q2 2018 In order to meet these service needs there must be integration with local health and Safety, stress management services, rehabilitation services, health and wellbeing and counselling services. Prevention – of ill health caused or exacerbated by work Timely intervention– easy and early treatment for the main cause of sickness absence. Rehabilitation – to help staff stay at work or return to work after illness Health Assessments for work– to help manage attendance, retirement and related matters Promotion of health and well being – using work as a means to improve health and well being and using the workplace to promote health Teaching and training – encouraging staff and managers to support staff health and well–being. Discussion: The role of the Workplace Health and Wellbeing is to progress the ' Hub and Spoke' model and to evaluate the effectiveness.